Development of Islamic Religious Education Learning Media Based on Smart Spinner Media at SDN 34 Negeri Katon, Pesawaran Regency - Rendy Yudha Pratama; Amir Syaifurrohman; Desi Permata Sari (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to develop and analyze the effectiveness of the Smart Spinner interactive learning media in improving students' learning outcomes Pendidikan Agama Islam at SDN 34 Negeri Katon, Pesawaran Regency. This research employed the ADDIE development model, consisting of five stages: analysis, design, development, implementation, and evaluation. The study involved 30 fourth-grade students selected purposively. The findings indicate that the Smart Spinner significantly improved students' learning outcomes, with an average pre-test score of 59.73 and a post-test score of 78.63. Expert validation revealed that this media achieved a high level of feasibility in terms of content, design, and interactivity. Additionally, feedback from teachers and students highlighted its ease of use, attractiveness, and effectiveness in enhancing learning motivation. This study concludes that the Smart Spinner is an effective learning tool for Islamic Religious Education. The sustainability potential of this research includes the development of digital-based media and its application to other subjects in broader educational settings.